The Relationship Between Mother's Knowledge About Milk Bottle Hygiene and the Incidence of Diarrhea in Infants Aged 6-12 Months in the Work Area of ​​Simpang Agung Health Center, Central Lampung Regency in 2024 - Abesti, Selly; Subardiah, Ida (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The high incidence of diarrhea in infants is a very serious problem that needs to be solved. One of the factors to reduce the risk of children developing diarrhea due to bottle-feeding is the presence of good and correct knowledge about bottle-feeding hygiene carried out by mothers. The purpose of this study was to determine the relationship between maternal knowledge about milk bottle hygiene and the incidence of diarrhea in infants aged 6-12 months in the Simpang Agung Health Center Working Area, Central Lampung Regency in 2024. The scope of this research is the scope of pediatric nursing. This study used quantitative methods with analytic design and cross sectional approach. The population in this study amounted to 67 mothers who had babies aged 6-12 months. The sample to be taken from the population is 40 mothers using purposive sampling technique. Based on the results of data analysis, it is known that the Simpang Agung Health Center in Central Lampung Regency in 2024, Most mothers had poor knowledge about the hygiene of milk bottles as much as 47.5% and children who experienced diarrhea as much as 45.0%. Based on the results of statistical tests, the p-value is 0.018 or p-value 0.05, which means that there is a relationship between maternal knowledge about the hygiene of milk bottles with the incidence of diarrhea in infants aged 6-12 months in the Simpang Agung Health Center Working Area, Central Lampung Regency in 2024. The results of this study can be used as information for health workers at the Puskesmas to conduct socialization to the visiting community regarding knowledge and behavior about the use of good milk bottles.